2003
DOI: 10.1080/15287390306415
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Activity of Various Diesel Exhaust and Ambient Particles in Two Allergic Models

Abstract: In the framework of an EU study entitled "Respiratory Allergy and Inflammation Due to Ambient Particles" (RAIAP), various collected particulate matter samples were to be tested for their adjuvant potency in two animal models of allergy. A pollen allergy model in the Brown Norway (BN) rat and an ovalbumin model in the BALB/c mouse were used in this study to compare the discriminatory value of these two models and to evaluate them for later studies of collected RAIAP-samples. Two different sources of diesel exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 47 publications
1
34
3
1
Order By: Relevance
“…Co-exposures to aeroallergens (such as grass pollen) and particles result in synergistic effects that lead to much stronger allergic responses in experimental animals and human beings than the sum of the responses to each of these constituents (D'Amato et al, 2005;Steerenberg et al, 2003;Diaz-Sanchez et al, 1999). However, this is different from studies in which the effects of particles have been studied on already allergic subjects.…”
Section: Pmmentioning
confidence: 43%
“…Co-exposures to aeroallergens (such as grass pollen) and particles result in synergistic effects that lead to much stronger allergic responses in experimental animals and human beings than the sum of the responses to each of these constituents (D'Amato et al, 2005;Steerenberg et al, 2003;Diaz-Sanchez et al, 1999). However, this is different from studies in which the effects of particles have been studied on already allergic subjects.…”
Section: Pmmentioning
confidence: 43%
“…PM adjuvant effects have been demonstrated in both animal and human studies (Diaz-Sanchez et al 1997;Gilliland et al 2004;Kleinman et al 2007;Matsumoto et al 2006;Steerenberg et al 2003aSteerenberg et al , 2003bStevens et al 2008;Whitekus et al 2002). Although in humans it has been shown that intranasal instillation of diesel exhaust particles (DEP) could enhance ragweed-induced immunoglobulin E (IgE) and interleukin-4 (IL-4) production, results from animal studies have demonstrated that low-dose challenge by aerosolized inhalation or intratracheal instillation could enhance allergic sensitization to an experimental allergen such as ovalbumin (OVA) (Diaz-Sanchez et al 1997;Gilliland et al 2004;Matsumoto et al 2006;Steerenberg et al 2003aSteerenberg et al , 2003bStevens et al 2008;Whitekus et al 2002).…”
mentioning
confidence: 99%
“…This hypothesis has not yet been formally tested in an in vivo model for PM adjuvant effects. In fact, most of the animal studies to date have used poorly calculated PM doses that far exceed the real-life exposure amounts and do not address the mechanism of the adjuvant effect (Ichinose et al 2004;Inoue et al 2005;Steerenberg et al 2003aSteerenberg et al , 2003b. Thus, we aimed to determine whether there is a positive correlation between the adjuvant effect of ambient concentrated PM and their content of redox cycling organic chemicals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The second allergy model is a lung allergy model with intranasal sensitization and challenge with ovalbumin (OVA). Whereas OVA alone induced OVA-specific IgE, lung pathology, and eosinophils in the BALF, coexposure of OVA and particulate matter (diesel exhaust particles, residual oil fly ash, and ambient particles) during the sensitization phase increased the size of these effects (33). Moreover, it has been described as a model for human lung allergy (14).…”
mentioning
confidence: 99%